Environmental degradation and economic growth: evidence for a developing country - Toledo Macas, E. (2016)
This paper examines the relationship between economic growth and environmental degradation in Ecuador from 1971 to 2010. We estimate this relationship in a country with a heavy reliance on revenue from the exploitation of natural resources, the depletion of vegetation cover in recent decades and a low level of participation of industry in GDP. We show the existence of an inverse relationship between real GDP and vegetation cover, indicating that the output of this country is based on environmental degradation. Through Johansen co-integration tests, we check that there is a relationship of long-term equilibrium between the first differences of real GDP, vegetal cover and the urbanization rate. The ECM shows that there is a short-term relationship between vegetation cover, the GDP and the rate of urbanization. Finally, we did not found Granger causality between the variables. A policy implication based on our findings is that policies to protect the environment should not jeopardize economic growth and not limit the rapid urbanization in the country. © 2016 Springer Science+Business Media Dordrecht